Review of current knowledge on strip-till cultivation and possibilities of its popularization in Poland - Różewicz, Marcin (Polish Journal of Agronomy, 2022)
In this review paper strip-till has been characterized from the point of view of the latest scientific research and practi- cal justification of the advisability of using and popularizing this cultivation method in Poland for various crop species. Analysis of scientific literature has shown that strip-till has a beneficial ef- fect on crops and soil properties. It reduces the number of tillage operations, and thus labour costs and fuel consumption. Further improvement of strip-till cultivation should be related to the im- provement of seeding units designed for this cultivation technol- ogy, as well as to the implementation of precision farming solu- tions related to the application of fertilizers and their effective use by plants. In connection with the implementation of cultivation technologies improving soil quality and reducing the negative im- pact of agriculture on the environment, strip-till technology has a chance to be much more widely used in Poland and may replace traditional plough tillage.